Patient*innenzentrierte perioperative Versorgung: perioperative Prozessqualität, Effektivität von Schmerztherapie und Mobilisationsfortschritt nach Implementation eines Maßnahmenbündels bei Knietotalendoprothese - Spielberger, J. (Anaesthesist, 2020)
BACKGROUND: The perioperative surgical home is a patient-centered, team-based model of care developed in the USA to coordinate diagnosis, treatment and follow-up; however, due to different healthcare systems, scientific findings in the USA cannot be simply transferred to Germany. OBJECTIVE: This preliminary study was carried out to evaluate the effects of a new interdisciplinary treatment bundle (patient-centered perioperative vigilance, PPV) in a German university hospital. MATERIAL AND METHODS: After IRB approval and written informed consent, 34 patients (PPV group) undergoing elective endoprosthetic surgery were enrolled after introduction of the PPV bundle (1. preoperative patient education, 2. specific surgical technique, 3. specific anesthesia technique, 4. start of mobilization on day of operation) and compared to historic matched pairs (HMP) for age cohort, ASA-PS, body mass index, and sex. We hypothesized that PPV shortens induction time (primary outcome). Secondary outcomes were length of hospital stay (LOS), resting pain and pain with movement on postoperative day 1 and mobilization progress on postoperative days 1, 3 and 6. Groups were compared with Wilcoxon-Mann-Whitney test for noninferiority. In the case of noninferiority, a Wilcoxon–Whitney–Mann test for superiority was additionally applied. RESULTS: The median anesthesia induction time was 13.5 min for PPV and 60 min for HMP (p < 0.0001). The LOS was 8 days for PPV and 12 days for HMP (p < 0.0001). Resting pain on postoperative day 1 was 20 for PPV (30 for HMP). Pain with movement was identical (median 40). Mobilization progress was better for PPV on days 1, 3 and 6 (p < 0.0001 for each day). CONCLUSION: The concept of patient-centered perioperative vigilance (PPV) shortens induction time and hospital length of stay. Mobilization improves with PPV on day 1. Higher pain scores in PPV seem to be clinically insignificant, which warrants further study.